IDENTIFICATION OF CHLOROPHYLL-A DISTRIBUTION FOR POTENTIAL FISHING ZONE BASED ON INTERPRETATION LANDSAT 8 IMAGERY IN KENDAL WATERS CENTRAL JAVA - Thonas Indra Maryanto; Anti Febriyanti (Fakultas Perikanan dan Kelautan, Universitas Riau, 2020)
Kendal District coastal and marine areas have considerable fishery potential. The potential of these fisheries can be explored well by taking into account several supporting factors. One of the factors that influence the level of fish existence is the condition of water fertility. The parameter used to determine the level of water fertility is to determine the chlorophyll-a content produced by phytoplankton. The development of remote sensing technology makes it possible to detect the presence of chlorophyll-a in waters with a large coverage and low cost. This study aims to identify the value of concentration and distribution of chlorophyll-a by using satellite landsat 8 imagery in four seasonal conditions, namely the west to east transition season, east season, east to west transition season and west season. The transition from West to East the minimum value of chlorophyll-a concentration is 1,106 mg / m3 and the maximum value is 2,700 mg / m3. East to West transition season has a minimum value of chlorophyll-a concentration of 1,539 mg / m3 and a maximum value of 2,700 mg / m3. The East Season has the same minimum and maximum values as the transition season from West to East but the amount of distribution differs, the West Season has a minimum value of chlorophyll-a concentration in this season of 1,318 mg / m3 and the maximum value of 2,700 mg /m3.